Digital thing as a “new” object of “new” civil legal relations - A. S. Slipchenko; S. O. Slipchenko (Law and Safety)
The article is devoted to theoretical comprehension and establishment of the concept of digital things as “new” objects of “new” civil legal relations which is proposed to be introduced into the civil legislation of Ukraine. It is obvious that in case of emergence of any new objects of civil rights which have become a prerequisite for the emergence of previously unknown relations, there is a need to establish an appropriate legal regime for such goods. Otherwise, the whole type of civil relations will remain unregulated, and this will have a negative impact not only on civil turnover, but will also create conditions for an increase in the number of violations of subjective rights. Therefore, the author analyses the legal relations which arise in the “digital environment” and which are proposed to be considered as new ones in the legal literature, and examines the objects of civil rights in such legal relations. The study concludes that the legal relations arising in the “digital environment” are fully covered by the already known types of civil legal relations and are not new in comparison with the existing ones, and a digital thing is not a new object of civil rights. It is just a new and additional name for long-known and even traditional objects of civil rights, including services, property rights, information, results of intellectual and creative activity, tradable objects of personal non-property legal relations, etc. The only peculiarity of virtual objects is that they are created and provided with the help of digital technologies, an Internet resource. It has been established that an online account is not an object of civil rights at all. It is only the result of recording data in the form of a digital code that allows computer equipment to identify, recognise a particular user and the limits of his/her access to certain Internet resources. A persistent computer (digital, electronic, software) code that is recorded in a database and located (stored) on a server is not an independent object of civil rights, but is only a record.